Squeeveillance: Performing Cuteness to Normalise Surveillance Power - Benjamin, Garfield (Surveillance & Society, 2024)
Cute videos are everywhere online. Many of these videos increasingly come from footage taken by doorbell cameras. Amazon’s Ring, and related connected camera devices, introduce new sociotechnical relations into domestic environments. First, I outline “squeeveillance” as the affective and performative dimensions of cuteness within surveillance. I explore the Ring surveillant assemblage and why it needs the power of cuteness. Then, I examine squeeveillance as the use of cuteness in the way Ring operates. I use the TV show Ring Nation (2022–present) to discuss the remediation of cute footage from doorbell cameras onto other media, before discussing the ways in which cuteness is performed as a normalisation of surveillance power. The article draws on theories of cuteness in conjunction with surveillance studies of power relations. In presenting squeeveillance as a lens through which to assess the expanding scope of Ring, I offer a discussion of the interconnected role of surveillance in contemporary domestic and media settings and its relation to current forms of power in surveillant assemblages.